Upaya Kepala Sekolah dalam Meningkatkan Mutu Pendidikan melalui Program Tahfidz di MI Al-Ma’shum Surakarta - Kinesti, Rakanita Dyah Ayu; Ro’fati, Delima Nailul; Syahrani, Mirna Bunga; Sakilah, Ainun (Lembaga Yasin AlSys, 2023)
The principal plays a role as an important factor influencing the improvement of the quality of education in schools through individual assistance in schools. The principal`s leadership describes the condition of the school. A leader has competency standards that must be possessed which include managing and leading competencies. The results of research on the efforts of school principals to improve the quality of education at MITTQUM through; 1) the existence of kuttab and regular programs, 2) facilities and infrastructure that support learning activities, 3) selecting the acceptance of new students, 4) recruitment of teaching and educational staff, 5) the program develops the talents and interests of students. This study aims to describe the efforts made by school principals in devoleping the quality of education through the tahfidz program at the Integrated MI Tahfizhul Qur`an Al-Ma`shum Surakarta. This study uses a qualitative descriptive method approach. Data collection tecniques using observation, interviews and documentation. Implementation carried out by the principal; discipline, regular meetings, rewards